Notes towards a connectionist program for the study of syntax - Ney, James W. (Lenguas Modernas, 2017)
A connectionist progran for the study of syntax would require a radical change in approaches to the subiect matter. This change would be necessitated by the fact that grammarians and linguists have traditionally looked at language as though it is processed in a serial fashion